Managing Constipation in Adults With Cancer - Wickham, Rita J. (J Adv Pract Oncol, 2017)
Constipation is common in individuals with cancer, occurring in almost 60% of patients overall. The incidence increases in patients with advanced disease, particularly in those receiving opioid analgesics or medications with anticholinergic properties. Constipation is not uniformly assessed and therefore not recognized and appropriately managed in many instances. This can increase patients’ physical and psychological distress. Furthermore, there is scant research to support current management strategies for constipation. The objectives of this review are to explore the incidence of and risk factors for constipation in patients with cancer, to discuss the extent of the problem, to explore the nonpharmacologic and pharmacologic measures for constipation and fecal impaction, and to synthesize a laxative management. An extensive review of medical, pharmacy, and nursing literature was done to explore the physiology and pathogenesis of constipation; detail the mechanisms of action, onset of effect, approximate costs, and adverse effects of drugs for constipation; and condense clinical expert consensus recommendations for constipation, particularly in patients with cancer. Advanced practitioners (APs) and other clinicians play crucial roles in identifying individuals at risk for and experiencing constipation to help them use effective regimens, including over-the-counter laxatives, and perhaps adjunctive nondrug measures. Clinicians and patients must develop an agreed-upon language for identifying the severity and effects of constipation. In addition, both should understand which laxatives are most appropriate and which should be avoided for particular patients. Two prescription agents are also available, and understanding when they should be used is important for APs.